2012
DOI: 10.1016/j.jcrs.2012.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Five-year clinical study of patients with pseudophakic monovision

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
0
17
0
1
Order By: Relevance
“…Using this method, the dominant eye is conventionally corrected for distance vision because it seems to be easier to suppress blur in the non-dominant eye than in the dominant eye 1. Monovision has been applied to corneal refractive surgery,2 3 and pseudophakic monovision has also been attempted 4 5. Pseudophakic monovision is a type of monovision used in cataract surgery to correct postoperative presbyopia using monofocal IOLs 6…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, the dominant eye is conventionally corrected for distance vision because it seems to be easier to suppress blur in the non-dominant eye than in the dominant eye 1. Monovision has been applied to corneal refractive surgery,2 3 and pseudophakic monovision has also been attempted 4 5. Pseudophakic monovision is a type of monovision used in cataract surgery to correct postoperative presbyopia using monofocal IOLs 6…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al. () found a positive correlation between preoperative near exophoria and postoperative stereopsis in near vision, demonstrating again the importance of a comprehensive preoperative evaluation.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies define preLI+ as a reduction of the exoangle by more than 40%,13 one-third14 or 20%4 6 compared with the primary gaze, while others set the criterion as an absolute deviation difference of >10 PD4 7 15 or ≥5 PD 16 17. We defined preLI+ as a reduction of the exodeviation by more than 5 PD in the preoperative condition and postLI+ as >5 PD of change in the postoperative condition compared with the primary gaze.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that preoperative significant LI (preLI+) is associated with surgical overcorrection in intermittent exotropia,1 6 some authors have suggested that preLI+ does not influence the surgical results 4 7. A significant degree of unilateral lateral rectus recession (ULR) is a potent risk for postoperative significant LI (postLI+), but there are few studies about change of LI after surgery 8–10…”
Section: Introductionmentioning
confidence: 99%